Multiscale Molecular Dynamics Simulation of Plasma Processing: Application to Plasma Sputtering - Brault, Pascal (Frontiers in Physics, 2018)
Molecular dynamics is an atomistic tool that is able to treat dynamics of atom/molecules/cluster assemblies mainly in the condensed and liquid phases. The goal of the present article is to provide a new methodology for describing all phenomena of plasma processing and beyond such as gas phase chemistry as well. Simulations of condensed matter and liquid processes by molecular dynamics are now readily accessible provided the interaction potentials are available, so quantitative parameters can be deduced as diffusion coefficient, … The situation is less clear for gas phase processes while they operate on larger space and time scales than for condensed phases and at lower specie densities. The present article is proposing a new methodology for describing plasma core interactions in taking into account experimental space and time scales. This is illustrated on a plasma sputtering process and deposition in a single simulation.